Convergent Adaptation in the Dominant Global Hospital Clone ST239 of Methicillin-Resistant Staphylococcus aureus - Sarah L. Baines (American Society for Microbiology, 2015)
ABSTRACT Infections caused by highly successful clones of hospital-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) are a major public health burden. The globally dominant sequence type 239 (ST239) HA-MRSA clone has persisted in the health care setting for decades, but the basis of its success has not been identified. Taking a collection of 123 ST239 isolates spanning 32 years, we have used population-based functional genomics to investigate the evolution of this highly persistent and successful clone. Phylogenetic reconstruction and population modeling uncovered a previously unrecognized distinct clade of ST239 that was introduced into Australia from Asia and has perpetuated the epidemic in this region. Functional analysis demonstrated attenuated virulence and enhanced resistance to last-line antimicrobials, the result of two different phenomena, adaptive evolution within the original Australian ST239 clade and the introduction of a new clade displaying shifts in both phenotypes. The genetic diversity between the clades allowed us to employ genome-wide association testing and identify mutations in other essential regulatory systems, including walKR, that significantly associate with and may explain these key phenotypes. The phenotypic convergence of two independently evolving ST239 clades highlights the very strong selective pressures acting on HA-MRSA, showing that hospital environments have favored the accumulation of mutations in essential MRSA genes that increase resistance to antimicrobials, attenuate virulence, and promote persistence in the health care environment. Combinations of comparative genomics and careful phenotypic measurements of longitudinal collections of clinical isolates are giving us the knowledge to intelligently address the impact of current and future antibiotic usage policies and practices on hospital pathogens globally. IMPORTANCE Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for innumerable drug-resistant health care-associated infections globally. This study, the first to investigate the evolutionary response of hospital-associated MRSA (HA-MRSA) over many decades, demonstrates how MRSA can persist in a region through the reintroduction of a previously unrecognized distinct clade. This study also demonstrates the crucial adaptive responses of HA-MRSA to the highly selective environment of the health care system, the evolution of MRSA isolates to even higher levels of antibiotic resistance at the cost of attenuated virulence. However, in vivo persistence is maintained, resulting in a clone of HA-MRSA able to resist almost all antimicrobial agents and still cause invasive disease in the heavily compromised hosts found in modern health care settings.